Uji Resistensi Nyamuk Aedes Aegypti terhadap Cypermethrin 0,05% di Pelabuhan Sungai Duku Pekanbaru - Handayani, Dedes (LPPM Hang Tuah Pekanbaru, 2023)
The use of chemical insecticides is one way to control the vector of dengue hemorrhagic fever that is caused by the Aedes aegypti mosquito. Considering that the use of different insecticides in an area will result in different resistance statuses, it is necessary to conduct a resistance test. The use of cypermethrin has replaced Malathion which is used at the Duku River Port, Pekanbaru. This study aims to determine the resistance status of the Aedes aegypti mosquito to the insecticide Cypermethrin at The Duku River Port, Pekanbaru. The method in this research is descriptive with a cross-sectional study design. The independent variable was the Aedes aegypti mosquito exposed to insecticide at the Duku River Port, while the dependent variable was the Aedes aegypti mosquito susceptibility status. The resistance test method refers to The World Health Organization Susceptibility Test criteria. The resistance test using WHO standard impregnated paper showed that the percentage of mosquitoes that died after being exposed to impregnated paper containing 0.05% Cypermethrin for 24 hours at the Duku River Port, Pekanbaru was 83%. There has been a tolerance for the use of Cypermethrin 0.05% against the population of Aedes aegypti mosquito in the Duku River Port, Pekanbaru.